The Effectiveness of Health Education on Coughing and Sneezing Etiquette on Student’s Knowledge and Behavior at SDIT Mutiara Hati in 2025 - Tatag Mulyanto; Safira Putri (Universitas Pahlawan Tuanku Tambusai, 2026)
Acute Respiratory Infections (ARI) remain one of the major health problems among schoolage children. Respiratory diseases can be transmitted through droplets emitted when coughing and sneezing, especially if proper etiquette is not followed. The busy school environment has the potential to accelerate the spread of disease if students have poor knowledge and behavior regarding coughing and sneezing etiquette. Therefore, health education is needed as a promotive and preventive measure to improve students knowledge and behavior from an early age. To determine the effectiveness of health education on coughing and sneezing etiquette on the knowledge and behavior of students at SDIT Mutiara Hati in 2025. This study used a quatitative method with a quasi-experimental design using a pretest and posttest approach. The research population consisted of all 61 third grade students at SDIT Mutiara Hati. The sampling technique used purposive sampling. Data collection was conducted using knowledge and behavior questionnaires. Data analysis was performed using univariate and bivariate analysis using the Wilcoxon test. The results of the study show an increases in the average knowledge score of students from 77,70 before the intervention to 90,49 after receiving health education. The Wilcoxon test result showed a p-value of 0.000 (p < 0.05), indicating a significant difference in knowledge before and after the intervention. For the behavior variable, a p-value of 0.000 (p < 0.05) was also obtained, indicating an increase in student behavior in applying coughing and sneezing etiquette. Health education on coughing and sneezing etiquette proved effective in improving the knowledge and behavior of students at SDIT Mutiara Hati in 2025. The findings of this study demonstrate that structured health education utilizing video media and interactive explanation is effective in significantly improving both knowledge and behavior regarding coughing and sneezing etiquette among third-grade students at SDIT Mutiara Hati. The statistically significant increase in knowledge scores and the positive shift in behavioral patterns toward more frequent and consistent application of proper etiquette highlight the intervention's impact. This suggests that targeted, age-appropriate educational programs in school settings can successfully enhance students' understanding and adoption of preventive respiratory hygiene practices. The results align with prior research emphasizing the role of early health education in fostering sustainable healthy habits, thereby contributing to infection control efforts within densely populated environments like schools. Consequently, integrating such interventions into routine school health promotion is recommended to mitigate the transmission of Acute Respiratory Infections (ARI) among children.